A Four-Step Model for the IL-6 Amplifier, a Regulator of Chronic Inflammations in Tissue-Specific MHC Class II-Associated Autoimmune Diseases - Murakami, Masaaki; Hirano, Toshio (Frontiers in Immunology, 2011)
It is thought autoimmune diseases are caused by the breakdown of self-tolerance, which suggests the recognition of specific antigens by autoreactive CD4+ T cells contribute to the specificity of autoimmune diseases. In several cases, however, even for diseases associated with class II MHC alleles, the causative tissue-specific antigens recognized by memory/activated CD4+ T cells have not been established. Rheumatoid arthritis (RA) and arthritis in F759 knock-in mouse line (F759 mice) are such examples, even though evidences support a pathogenic role for CD4+ T cells in both diseases. We have recently shown local events such as microbleeding together with an accumulation of activated CD4+ T cells in a manner independent of tissue antigen-recognitions induces arthritis in the joints of F759 mice. For example, local microbleeding-mediated CCL20 expression induced such an accumulation, causing arthritis development via chronic activation of an IL-17A-dependent IL-6 signaling amplification loop in type 1 collagen+ cells that is triggered by CD4+ T cell-derived cytokine(s) such as IL-17A, which leads to the synergistic activation of STAT3 and NFκB in non hematopoietic cells in the joint. We named this loop the IL-6-mediated inflammation amplifier, or IL-6 amplifier. Thus, certain class II MHC–associated, tissue-specific autoimmune diseases may be induced by local events that cause an antigen-independent accumulation of effector CD4+ T cells followed by the induction of the IL-6 amplifier in the affected tissue. To explain this hypothesis, we have proposed a Four Step Model for MHC class II associated autoimmune diseases. The interaction of four local events results in chronic activation of the IL-6 amplifier, leading to the manifestation of autoimmune diseases. Thus, we have concluded the IL-6 amplifier is a critical regulator of chromic inflammations in tissue specific MHC class II-associated autoimmune diseases.